Caregivers’ experience of having a child with Down syndrome: a meta-synthesis - Xiao Nan Zhang; Shuo Zhang; Chun Yan Liu; Zhi Hong Ni; Hai Tao Lv (BMC Nursing)
Abstract Background This study aimed to integrate the experiences of caregivers of children with Down syndrome during the care process and understand their feelings and needs. Methods We used Page et al.’s (2021) Preferred Reporting Items for Systematic Reviews and Meta-synthesis Statement. Ten databases (Web of Science, PubMed, EMBASE, Cochrane Library, CINAHL, PsycInfo, China Biology Medicine, China National Knowledge Infrastructure, Wanfang Data, and China Science and Technology Journal Database) were searched for relevant studies published from the inception of the database to October 2023. Eight qualitative studies were analysed. The following seven themes were included: ‘feeding pressure’, ‘hope for education’, ‘societal rejection and stigma’, ‘psychological pressure’, ‘caring burden’, ‘family burden’, and ‘family adaptation and self-growth’. Results We found that feeding pressures, educational concerns, language difficulties, and discrimination and stigmatisation led to psychological, economic, and family stress in caregivers of children with Down syndrome. We document the need for strong coping mechanisms and support systems for these families from medical and psychological institutions and a need for public education and awareness. Conclusions We summarised the daily care experiences of caregivers of children with Down syndrome. Our findings provide a scientific basis for further research focused on reducing physical and mental pressure on caregivers and improving the quality of family life.